2023
DOI: 10.1111/dom.15431
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world effectiveness and safety of oral semaglutide in people living with type 2 diabetes: A nationwide multicentre retrospective observational study (ENDO2S‐RWD)

Oscar Moreno‐Pérez,
Rebeca Reyes‐Garcia,
Inés Modrego‐Pardo
et al.

Abstract: BACKGROUNDType 2 diabetes guidelines recommend glucagon-like peptide-1 receptor agonists (GLP-1 RAs) and/or sodium-glucose co-transporter-2 inhibitors for people living with type 2 diabetes (PLWT2D) with an

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
1
2
1
Order By: Relevance
“…Trying to compare the results of the present work with those of RCT trials, it appears that the relatively small series of data obtained are in line with the RCT observations in terms of both efficacy and safety. Considering other real-world studies on T2D patients, in reference to glycemic control, in the present work, the HbA1c reduction at 6 months (−0.68%) was comparable to that shown in the ENDO2S-RWD [21] (−0.7%HbA1c) and in a recent study by Frazer and colleagues [22] (−0.8%). Limiting the comparison to the Italian evidence available, the present cohort reached the greatest glycemic efficacy (−0.3% and −0.4%) [23,24]; conversely, a more effective glycemic control was reported by the IGNITE study [18] (−0.9%), the PIONEER REAL Switzerland [19] (−0.91%), and in a cohort of Japanese T2D patients [20] (−1.24%).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Trying to compare the results of the present work with those of RCT trials, it appears that the relatively small series of data obtained are in line with the RCT observations in terms of both efficacy and safety. Considering other real-world studies on T2D patients, in reference to glycemic control, in the present work, the HbA1c reduction at 6 months (−0.68%) was comparable to that shown in the ENDO2S-RWD [21] (−0.7%HbA1c) and in a recent study by Frazer and colleagues [22] (−0.8%). Limiting the comparison to the Italian evidence available, the present cohort reached the greatest glycemic efficacy (−0.3% and −0.4%) [23,24]; conversely, a more effective glycemic control was reported by the IGNITE study [18] (−0.9%), the PIONEER REAL Switzerland [19] (−0.91%), and in a cohort of Japanese T2D patients [20] (−1.24%).…”
Section: Discussionsupporting
confidence: 88%
“…Indeed, gastrointestinal side effects were experienced by 13.5% of patients, leading to treatment discontinuation in the 20.8% of cases; thus, gastrointestinal illness represents the primary reason for treatment interruption. The discontinuation rate observed in the present study is slightly higher than that observed in both the PIONEER program and the available observational studies with oral semaglutide [ 18 , 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Given the global supply chain issues for subcutaneous GLP1RAs, oral semaglutide could also be an option. Real-world data show that it is effective and safe in an unselected population, with one-third reaching WL >10% and near two-thirds achieving HbA1c <7% [ 60 ].…”
Section: Therapeutic Translation: Dysfunctional Adipose Tissue Approa...mentioning
confidence: 99%